EFFECT OF PLAY THERAPY ON ANXIETY IN FACING HOSPITALIZATION ON PRESCHOOL CHILDREN AGED 3-6 YEARS (Study in Seruni room of Jombang hospital) - Diah Ayu Nurvita; Emi Kusumawardani; Dwi Puji (Jurnal Keperawatan, 2014)
Anxietyin childrencanslow the healing process, decreasing of recovered spirit and uncooperative of childrenon themaintenance action. The result of preliminary studied om Seruni room of Jombang hospital were 28pre-school children patients experienced fear when nurse came and crying when done action and they hadno appetite. The effect of hospitalization and anxiety which experienced by pre-school children can disturbchild development and healing process on children. The purpose of this researach was to determine the effectof play therapy on anxiety in facing hospitalization on pre-school children aged 3-6 years in Seruni room ofJombang hospital.This research design was one group pre – post test experimental with population of allpre-school children patients aged 3-6 years in Seruni room of Jombang hospital totaled as 40 children andthe total sample as many as 20 respondents with simple random sampling technique, the variable in thisreseach consisted of 2 variables those were independent variable that’s providing therapy on patientsappropriateproceduresspecific actionsperformed and dependent variable was the anxiety levelsof patients,while data collection used a questionnaire and check list. Statistical test used wilcoxon test.The results obtained most of respondents were 11 anxiety people (55%) before given playing therapy wereheavy and entirely respondents were 20 anxiety people (100%) after provided playing therapy were mild,while based on wilcoxon result test with SPSS obtained (= 0,000) so H1 accepted that meant there was aneffect of play therapy in facing hospitalization on pre-school aged children.The conclusion of this reseach is there was an effect of play therapy on anxiety in facing hospitalization onpre-school children aged 3-6 years in seruni room of Jombang hospital.It is expected to health worker canexpand and apply play therapy to decrease the impact of hospitalization on children and also utilize facilitiesof hospital conducting play therapy.Keywords : Play Therapy, Anxiety, Hospitalization, Pre-School Children